Leptin- or troglitazone-induced lipopenia protects islets from interleukin 1beta cytotoxicity. - Shimabukuro, M (1997)
Interleukin 1beta (IL-1beta)-induced beta cell cytotoxicity has been implicated in the autoimmune cytotoxicity of insulin-dependent diabetes mellitus. These cytotoxic effects may be mediated by nitric oxide (NO). Since long-chain fatty acids (FFA), like IL-1beta, upregulate inducible nitric oxide synthase and enhance NO generation in islets, it seemed possible that islets might be protected from IL-1beta-induced damage by lowering their lipid content. We found that IL-1beta-induced NO production varied directly and islet cell viability inversely with islet triglyceride (TG) content. Fat-laden islets of obese rats were most vulnerable to IL-1beta, while moderately fat-depleted islets of food-restricted normal rats were less vulnerable than those of free-feeding normal rats. Severely lipopenic islets of rats made chronically hyperleptinemic by adenoviral leptin gene transfer resisted IL-1beta cytotoxicity even at 300 pg/ml, the maximal concentration. Troglitazone lowered islet TG in cultured islets from both normal rats and obese, leptin-resistant rats and reduced NO production and enhanced cell survival. We conclude that measures that lower islet TG content protect against IL-1beta-induced NO production and cytotoxicity. Leptin or troglitazone could provide in vivo protection against insulin-dependent diabetes mellitus.